Assessment of maternal birth satisfaction and intra-partum experiences among the women of rural areas of Tamil Nadu- a cross sectional study - Marimuthu, Janakiram; Murugan, A. Arul (International Journal Of Community Medicine And Public Health, 2021)
Background: Childbirth, though a physiological process, has been associated with multiple risks and stress on the women, even before the time of conception till the post-partum. Every woman around the world has a right to receive respectful maternity care. Birth satisfaction and respectful maternal care has direct impact on percentage of institutional deliveries. There is paucity of studies conducted among the women of rural Tamil Nadu regarding birth satisfaction and intrapartum experiences. Methods: A cross-sectional study was conducted in primary health center area, red hills among the post-partum women attending the immunization OPD at 6, 10 and 14th week after delivery during the months of March to June 2018. By simple random sampling technique 195 subjects were included. A semi-structured questionnaire was administered to collect the data. Ethical clearance was obtained from our Institutional Ethics Committee. Data was entered in MS Excel and analysis was done using SPSS Software version 23. Results: The study shows the importance of maternal satisfaction and intrapartum experiences of women in rural areas. It concluded that the overall satisfaction was 85.5%. The transport facility available at the health care set up which satisfied the mothers was around 91.4%. The interaction of health care providers with mothers during delivery was around 64.5%. Cleanliness and comfort of the delivery area was around 64%. Equality of care provided at the health care set up was around 83%. Conclusions: Reasons for delivery visit, duration of labour, and mode of delivery are independent predictors of maternal satisfaction.